Oil and its uses among the Arabs Historical study (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our greatest Messenger, Muhammad, and upon his pure and pure family, his noble and noble companions, and whoever follows his Sunnah until the Day of Judgment.The homeland of the Arabs has been distinguished throughout history for its oil wealth, which is the elixir of life and a source of energy. The Arabs were the first to discover oil, so they extracted it and collected it with their available means within the historical time periods. Researchers’ studies contributed to the origin of oil, its origin, and its locations in the land of the Arabs. It is a great turning point, while the study of the historical aspect of oil The role of the Arabs and their activity in developing their applied uses of oil is of beneficial importance and sheds light in the search for that.